The Role of Saliency in Learning First Words - Wildt, Eugenia; Rohlfing, Katharina J.; Scharlau, Ingrid (Frontiers in Psychology, 2019)
In word learning, one key accomplishment is the reference, that is, the linking of a word to its referent. According to classical theories, the term reference captures a mental event: A person uses a word to mentally recall a concept of an entity (an object or event) in order to bring it into the mental focus of an interaction. The developmental literature proposes different approaches regarding how children accomplish this link. Although researchers agree that multiple processes (within and across phonological, lexical, and semantic areas) are responsible for word learning, recent research has highlighted the role of saliency and perception as crucial factors in the early phases of word learning. Generally speaking, whereas some approaches to solving the reference problem attribute a greater role to the referent’s properties being salient, others emphasize the social context that is needed to select the appropriate referent. In this review, we aim to systematize terminology and propose that the reason why assessments of the impact of saliency on word learning are controversial is that definitions of the term saliency reveal different weightings of the importance that either perceptual or social stimuli have for the learning process. We propose that defining early word learning in terms of paying attention to salient stimuli is too narrow. Instead, we emphasize that a new link between a word and its referent will succeed if a stimulus is relevant for the child.